Oil prices and the US economy: Where is the boom? - Vipin Arora (Kiel Institute for the World Economy (IfW), 2015)
The author argues that the economic benefits of low gasoline prices for the U.S. economy have fallen substantially since the reemergence of America as a major oil producer. The old rule-ofthumb that a 10% fall in the oil price raises inflation-adjusted U.S. GDP by 0.2% is too large - the impact on economic activity should be closer to zero, and may even be negative if consumption grows slowly. The reasons for this change are straightforward, if underappreciated: (i) the value of oil production accounts for a larger share of the U.S. economy; and (ii) consumers are not spending the windfall like they used to because of higher debt levels, limited access to credit, slow wage growth, and an older population.
Keywords: C67; E20; E60; Q43; 330; oil price; economic activity; input-output; consumption